THE CONCEPT ANALYSIS OF RELIGIOUS MODERATION BY KH. HASYIM MUZADI AND ITS RELEVANCE TO THE RELIGIOUS MODERATION MODULE OF THE MINISTRY OF RELIGIOUS AFFAIRS - Mardiansyah, Tri; Fadlullah, Muhammad Endy (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Religious moderation is a unique concept for Islam in Indonesia. One of the figures who sparked this concept was Hasyim Muzadi. Through his work we can find out what must be done to create a life order based on religious moderation. Through the Religious Moderation Module, the Ministry of Religion of the Republic of Indonesia seeks to translate the concepts that have been initiated by national leaders so that they can be implemented in society, especially in education. This research is library research. The primary data is taken from the text in the book Islam Sejati Islam dari Hati by Hasyim Muzadi and the ModerasI Beragama Module of the Ministry of Religion of the Republic of Indonesia in 2019. The concept of religious moderation KH. Hasyim Muzadi according to indicators of religious teachings that are not excessive include; al-hanifiyyah and al-samhah (straight and tolerant) and anti-extremism. As for the indicators in the context of multiculturalism and multi-religion include; Ukhuwwah bayna al-din, Islam as rahmah lil-'alamin (a mercy to the universe), lita'arafu (knowing each other), and cultural acculturation. As for the indicators of religious education which are moderate and integrated with Pancasila values ??include; love for the motherland, al-istiqamah wa al-musawa (straight and equal), democracy. The concept of religious moderation of the Ministry of Religion of the Republic of Indonesia according to indicators of national commitment includes; the relationship between religion and the State, as well as acceptance of the four pillars of nationality. As for the indicators of tolerance include; moderate attitude in religion and the concept of wasathiyyah. Non-violence indicators include; fair and balanced, and anti-extremist ideology. According to accommodative indicators of local culture include; moderation in religious traditions and practices. The relevance of the concept of religious moderation KH. Hasyim Muzadi with the Indonesian Ministry of Religion located at; strengthening moderate religious understanding, efforts to prevent and overcome radicalism, and strengthen national commitment.